Answer: 17
================================
How I got that answer:
(2,3) and (3,1) have '3' in common in that the y value of the first pairs with the x value of the second.
If you picture a chain, then you start with x = 2, move to y = 3, then move to x = 3 and then y = 1
2 ---> 3 ---> 3 ---> 1
So f(f(2)) = f(3) = 1
If g(x) = f(f(x)), then we know (2,1) is on the graph of g(x)
-------------------------
Repeat for (3,1) and (1,5)
3 ---> 1 ---> 1 ---> 5
f(3) = 1
g(x) = f(f(x)) = f(f(3)) = f(1) = 5
We know that (3,5) is on the graph of g(x)
-------------------------
The two points on g(x) are: (2,1) and (3,5)
Comparing that to (a,b) and (c,d) we can see
a = 2, b = 1, c = 3, d = 5
a*b + c*d = 2*1 + 3*5 = 2 + 15 = 17